Treatment of Severe Hip Dysplasia with Leg Length Discrepancy Using Spherical Periacetabular Osteotomy - Yu Takeda; Tomokazu Fukui; Shigeo Fukunishi (Case Reports in Orthopedics)
Case. A 20-year-old woman with severe subluxation of the hip displayed a leg length discrepancy of approximately 20 mm. The proposed treatment was a spherical periacetabular osteotomy (SPO) for joint preservation and postoperative leg length maintenance. SPO is a novel periacetabular osteotomy procedure. At her 3-year follow-up, the patient had functional, pain-free motion and high satisfaction. In this case, the SPO technique was able to achieve satisfactory clinical results without further exacerbating the leg length discrepancy after surgery.